INVESTIGATION OF PHYSICAL AND MECHANICAL PROPERTIES OF INDIGENOUS DENTAL CERAMICS USED IN PAKISTAN - Dr Fatima Suhaib; Dr Madeeha Jamil; Dr Zahra Shafqat; Dr Amna Mehwish Ikram; Dr Mehvish Sajjad; Dr Zenab Yaasir (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundAlthough Pakistan uses indigenous dental ceramics extensively for restorative operations, little is known about their mechanical and physical characteristics.ObjectiveTo evaluate and compare the flexural strength, surface hardness, fracture resistance, and microstructure of commonly used indigenous dental ceramics in Pakistan.MethodologyA descriptive experimental study was conducted at the Department of Dental Materials, Lahore, from January to June 2024. Tests were conducted on 108 ceramic specimens from five domestic brands: VitaPak Zir (Brand E), SmileCraft Ceram (Brand D), BioZir Elite (Brand C), DentalStone Ceram (Brand B), and PacCeram Plus (Brand A).  Specimens were produced in accordance with ISO 6872.  Three-point bending was used to measure flexural strength, Vickers microhardness testing was used to measure surface hardness, and compressive loading to failure was used to measure fracture resistance.  Scanning electron microscopy was used to analyze microstructural features (SEM).  One-way ANOVA, post-hoc Tukey testing, and descriptive statistics were used in the data analysis, with significance set at p < 0.05.ResultsAll investigated attributes showed significant differences between the brands (p < 0.05). Vickers hardness (645 ± 22 VHN), fracture resistance (920 ± 35 N), flexural strength (158.4 ± 9.3 MPa), and mean grain size (1.6 ± 0.2 µm) were all greatest for Brand C. In all of these categories, Brand D had the lowest values. While Brand D had more porosity and microcracks, Brand C's better microstructure with less porosity and no microcracks was validated by SEM examination.ConclusionSignificant variability exists among indigenous dental ceramics, with some brands offering superior mechanical properties suitable for durable restorative use.